2009
DOI: 10.5194/bg-6-2743-2009
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of dissolved organic carbon and nitrogen fluxes in deciduous and coniferous forests under historic high nitrogen deposition

Abstract: Abstract. Numerous recent studies have indicated that dissolved organic carbon (DOC) and nitrogen (DON) play an important role in C and N cycling in natural ecosystems, and have shown that N deposition alters the concentrations and fluxes of dissolved organic substances and may increase leaching losses from forests. Our study was set up to accurately quantify concentrations and flux patterns of DOC, DON and dissolved inorganic nitrogen (DIN) in deciduous and coniferous forest in Flanders, Belgium, under histor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…This range is similar to that observed in the UK, between 20 and 50 % (Cape et al, 2004;González Benítez et al, 2009;Vanguelova et al, 2010). Other recent European studies have shown up to 15 % at the Belgian coast (Bencs et al, 2009) and 30 % in Flanders, Belgium (Sleutel et al, 2009), 23 % in the Czech Republic (Kopacek et al, 1997), 38 % in Poland (Kram, 2008), between 17 % and 23 % in the eastern Mediterranean (Mace et al, 2003;Violaki et al, 2010), 8 % in Germany (Michalzik and Matzner, 1999) and between 14 % and 41 % in Finland (Mustajarvi et al, 2008;Piirainen et al, 1998). The available data are shown in Fig.…”
Section: Comparison With the Literaturesupporting
confidence: 73%
“…This range is similar to that observed in the UK, between 20 and 50 % (Cape et al, 2004;González Benítez et al, 2009;Vanguelova et al, 2010). Other recent European studies have shown up to 15 % at the Belgian coast (Bencs et al, 2009) and 30 % in Flanders, Belgium (Sleutel et al, 2009), 23 % in the Czech Republic (Kopacek et al, 1997), 38 % in Poland (Kram, 2008), between 17 % and 23 % in the eastern Mediterranean (Mace et al, 2003;Violaki et al, 2010), 8 % in Germany (Michalzik and Matzner, 1999) and between 14 % and 41 % in Finland (Mustajarvi et al, 2008;Piirainen et al, 1998). The available data are shown in Fig.…”
Section: Comparison With the Literaturesupporting
confidence: 73%
“…Vitousek and Howarth, 1991;Aber et al, 1998Aber et al, , 2003Magill et al, 2004). These studies often find that DOC concentration in soil solution increases with elevated N deposition (Yano et al, 2000;McDowell et al, 2004;Pregitzer et al, 2004;Adams et al, 2005;Findlay, 2005;Sleutel et al, 2009;Rappe-George et al, 2013).…”
Section: Lu Et Al: Long-term Nitrogen Addition Decreases Carbon Lmentioning
confidence: 99%
“…To explore the importance of DOC effluxes under elevated N deposition in forest ecosystems, ecologists have conducted such studies by the methods of simulating N deposition or using natural N deposition gradients (Evans et al, 2008;Sleutel et al, 2009). Until now, these studies are limited to DOC dynamics (e.g.…”
Section: Lu Et Al: Long-term Nitrogen Addition Decreases Carbon Lmentioning
confidence: 99%
“…In the last decade the number of research papers addressing the evaluation of organic nitrogen in precipitation has increased and the mosaic of our knowledge is being continuously supplemented (Neff et al 2002;Cornell et al 2003;Cape et al 2004;Zhang et al 2008;Bencs et al 2009;Benitez et al 2009Benitez et al , 2010Pelster et al 2009;Sleutel et al 2009;Violaki et al 2010).…”
Section: Institute Of Forest Ecology Faculty Of Forestry and Wood Tementioning
confidence: 99%